2012
DOI: 10.1111/j.1540-5982.2011.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial effects of foreign direct investment in US states

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
(54 reference statements)
0
25
0
1
Order By: Relevance
“…Recently, some studies tested FDI spatial spillovers on productivity or economic growth and confirmed their existence (Madariaga and Poncet ; Bode et al. ).…”
Section: Spillover Channels and Empirical Evidencementioning
confidence: 91%
See 1 more Smart Citation
“…Recently, some studies tested FDI spatial spillovers on productivity or economic growth and confirmed their existence (Madariaga and Poncet ; Bode et al. ).…”
Section: Spillover Channels and Empirical Evidencementioning
confidence: 91%
“…Bode et al. 's () research, using data for US states from 1977–2003 and including spatial interdependence, indicates that inward FDI generates positive externalities on domestic TFP.…”
Section: Spillover Channels and Empirical Evidencementioning
confidence: 99%
“…Bode et al (2012) find spatial proximity to be important for spillovers from foreign firms operating in US states. Several earlier studies suggest that FDI intensified the spatial clustering of industrial activity within the United States by locating where agglomeration economies could be reaped (e.g., Coughlin et al 1991;Head et al 1995;Bobonis and Shatz 2007).…”
Section: Department Of Industrial Promotion and Policy (Dipp) Of The mentioning
confidence: 99%
“…Complementary to the evidence reported by Ö zyurt (2008), there is a growing literature with respect to third-country effects of FDI activity (see, e.g., Baltagi, Egger and Pfaffermayr 2007;Garretsen and Peeters 2009;Shepotylo 2010). Using regional data, Bode, Nunnenkamp, and Waldkirch (2011) analyze spatial effects of FDI and other Marshallian externalities on regional productivity growth among US states. The authors find that spatial effects shape these externalities significantly and help avoid drawing false policy conclusions.…”
Section: Theory and Empirics Of Productivity-trade-fdi Linkagesmentioning
confidence: 99%
“…Variables denoted by ''$ '' indicate weighted averages of values for spatial proximate neighbors. In modeling A 0i;t , we draw on Bode, Nunnenkamp, and Waldkirch (2011) and create it from the following terms: A 0;i represents the productivity effects of time-invariant location factors, e mt captures the common productivity effects of exogenous technological progress. The last term in equation (3) measures interregional productivity spillovers.…”
mentioning
confidence: 99%